The obstacles of teaching informatics in the new curricula to education ministry in Syrian Arabic Republic from the point of view of the teachers of this article. (A Field Study in Secondary Schools in Lattakia ) - Gnad , Rawah; Nassour , Rkdaa; Khrema, Mayssaa (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This study aims to identify the obstacles facing the computer teachers in the course of their teaching of the new curriculum. The researcher depend on descriptive approach , so designed a questionnaire consisting of 33 questions divided into four areas: The field of the student, teacger area, curriculum area, the field of the classroom environment. Where the sample of the study consisted of 120 teachers of computer science in the city of Lattakia. The results showed that there are many problems facing computer teachers and limit their ability to deliver information to students as required. The results showed that the main obstacles facing the computer teachers from their point of view are the weakness of the ability of students to use the computer. And teachers ' lack of knowledge of computer software. There is also a knowledge gap between the curriculum of the computer and the previous cognitive background of the students on this subject. And the lack of sufficient hardware in the computer lab. This study presented a set of conclusions and suggestions that help to alleviate these constraints.